Risk factors for surgical site infections after abdominal gynecologic surgeries (Latakia University Journal -Medical Sciences Series, 2019)
Background: The purpose of this study was to identify risk factors for surgical site infection (SSI) after abdominal gynecologic surgeries at the Department of obstetrics and gynecology in Tishreen hospital , Lattakia. Methods: A prospective study was initiated to investigate risk factors for SSI at a Tishreen hospital from february 2018 to February 2019 . All patients were followed up from the time of admission until the time of discharge and 30 days postoperatively to inspect the incidence of SSI. The chi-square test for categorical variables was used to determine the significance of association, whereas the multivariate logistic regression model was used to examine independent risk factors for SSI. Results: A total of 323 patients met the inclusion criteria, in whom 12 cases of infection occurred (3,7%) . Univariate analysis showed that SSI was associated with the duration of surgery, diabetes, cancer, postoperative drainage, age , and the duration between shaving and the surgery . Multivariate analysis identified four independent parameters correlating with the occurrence of SSI: diabetes (odds ratio [OR] 4,5; 95% confidence interval [CI] 1,3-15,8 ; P=0.007); cancer (OR 8 ; 95% CI 2,2 – 29,6 ; P=0.0001 ); operative duration more than 60 minutes (OR 5,6 ; CI 1,2 – 26,2 ; P=0.001); and postoperative drainage (OR 4,2 ; CI 1,3 – 13,8; P=0.03). Conclusion: Our data suggest that all these risk factors could be regarded as potential indicators of SSI and that relevant preventive measures should be taken to reduce SSI and improve patient outcomes. أهمية البحث وأهدافه : تحديد عوامل الخطورة المؤدية لحدوث انتانات الجروح بعد العمليات الجراحية البطنية النسائية قي قسم التوليد وأمراض النساء في مستشفى تشرين الجامعي باللاذقية . طريقة البحث : دراسة وصفية مستقبلية لتحديد عوامل الخطورة لدى المريضات اللواتي خضعن لعمل جراحي نسائي عن طريق البطن في قسم التوليد وأمراض النساء في مستشفى تشرين الجامعي في اللاذقية خلال الفترة الممتدة من شباط 2018 ولغاية شباط2019 ومتابعتهم لمدة شهر بعد العمل الجراحي لتقصي حدوث انتان الجرح ومعرفة عوامل الخطورة لديهم . وتم استخدام اختبار كاي مربع (chi- square ) للمتغيرات الفئوية لتحديد وجود علاقة ارتباط هامة بين عامل الخطورة وانتان الجرح بعد العمل الجراحي , بينما استخدمت معادلة الانحدار اللوجستي متعدد المتغيرات لدراسة عوامل الخطورة المستقلة لانتان الجروح بعد العمل الجراحي . النتائج : شارك في الدراسة 323 مريضة من اللواتي خضعن لعمل جراحي نسائي عن طريق البطن . بلغ عدد المريضات اللواتي طورون الانتان 12مريضة بمعدل حدوث 3.7% . أظهر التحليل وحيد المتغير وجود علاقة هامة بين انتان الجرح ونوع العمل الجراحي , مدة العمل الجراحي , الداء السكري , وجود المفجر , البدانة , التقدم بالعمر , المدة الفاصلة بين الحلاقة و العمل الجراحي . أما التحليل متعدد المتغيرات أظهر وجود 4 عوامل خطورة مستقلة تؤدي لحدوث انتان الجرح بعد العمل الجراحي : نوع العمل الجراحي (P = 0,0001 OR = 8 , CI [2,2 – 29,6 ] , ) مدة العمل الجراحي (OR = 5,6 , CI = [1,2-26,2] , P = 0,001 ) الداءالسكري OR = 4,5, CI = [1,3-15,8] , P = 0,007) ) وجود المفجر OR =4.2 , CI = [1,3-13,8] , P = 0,03 ) ) الخلاصة : أظهرت الدراسة أن العوامل المذكورة يمكن اعتبارها عوامل خطورة هامة لانتان الجروح بعد العمل الجراحي ويجب اتخاذ التدابير الوقائية اللازمة للحد من الانتان وتحسين نتائج العمل الجراحي .